2021
DOI: 10.1007/s10456-021-09777-7
|View full text |Cite
|
Sign up to set email alerts
|

SMAD6 transduces endothelial cell flow responses required for blood vessel homeostasis

Abstract: Fluid shear stress provided by blood flow instigates a transition from active blood vessel network expansion during development, to vascular homeostasis and quiescence that is important for mature blood vessel function. Here we show that SMAD6 is required for endothelial cell flow-mediated responses leading to maintenance of vascular homeostasis. Concomitant manipulation of the mechanosensor Notch1 pathway and SMAD6 expression levels revealed that SMAD6 functions downstream of ligand-induced Notch signaling an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 59 publications
5
47
0
Order By: Relevance
“…Recently, an additional role of SMAD6 in endothelial cell homeostasis was reported using different human endothelial cell cultures. This work showed that SMAD6 is required when vessels transition from an angiocrine state to a homeostatic maintenance state as a transducer of endothelial cell flow-mediated responsesdownstream of the mechanosensory Notch1 [124]. These different effects of SMAD6 might contribute to the distinct context-dependent functions of BMP signaling in angiogenesis.…”
Section: Inhibitory Smads (I-smads)mentioning
confidence: 86%
See 1 more Smart Citation
“…Recently, an additional role of SMAD6 in endothelial cell homeostasis was reported using different human endothelial cell cultures. This work showed that SMAD6 is required when vessels transition from an angiocrine state to a homeostatic maintenance state as a transducer of endothelial cell flow-mediated responsesdownstream of the mechanosensory Notch1 [124]. These different effects of SMAD6 might contribute to the distinct context-dependent functions of BMP signaling in angiogenesis.…”
Section: Inhibitory Smads (I-smads)mentioning
confidence: 86%
“…For instance, BMP4 is strongly downregulated in laminar shear stress conditions in vascular endothelial cells, whereas it is induced under disturbed flow conditions [123]. Moreover, recently, it has been shown that Notch1-mediated upregulation of SMAD6 is necessary for flow-mediated alignment, homeostatic quiescence and the barrier function of blood endothelial cells [124].…”
Section: Mechano-transductionmentioning
confidence: 99%
“…BMP signaling through SMAD1/5 upregulates expression of SMAD6 and SMAD7, which creates a negative feedback loop for the BMP signaling pathway [ 108 ]. SMAD6 expression is also upregulated by Notch signaling in endothelial cells [ 109 , 110 ]. SMAD6 and SMAD7 can regulate BMP signaling in several ways.…”
Section: Chapter 1: Bmp Signaling In Blood Vessels—the Playersmentioning
confidence: 99%
“…Fig. 2H), that functions downstream of NOTCH-signaling to downregulate proliferation and induce junction-associated genes (Ruter et al, 2021).…”
Section: Supplementary Notementioning
confidence: 99%